2018
DOI: 10.1007/s00726-018-2614-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and combined metformin and l-citrulline supplementation on l-arginine-related pathways in Becker muscular dystrophy patients: possible biochemical and clinical implications

Abstract: The L-arginine/nitric oxide synthase (NOS) pathway is considered to be altered in muscular dystrophy such as Becker muscular dystrophy (BMD). We investigated two pharmacological options aimed to increase nitric oxide (NO) synthesis in 20 male BMD patients (age range 21-44 years): (1) supplementation with L-citrulline (3 × 5 g/d), the precursor of L-arginine which is the substrate of neuronal NO synthase (nNOS); and (2) treatment with the antidiabetic drug metformin (3 × 500 mg/d) which activates nNOS in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 73 publications
6
40
0
Order By: Relevance
“…Interestingly, a recent study also showed that the levels of L-arginine and its precursor L-citrulline were significantly lower in mdx muscles with respect to wild type ones [64]. A recent study showed that L-homoarginine (one of the direct products of L-Arg metabolism in human) serum levels were significantly lower in Becker muscular dystrophy patients [61]. This evidence, if confirmed in DMD patients, might give more support to the requirement of L-arginine and L-citrulline supplementation through diet.…”
Section: L-arginine and L-citrullinementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study also showed that the levels of L-arginine and its precursor L-citrulline were significantly lower in mdx muscles with respect to wild type ones [64]. A recent study showed that L-homoarginine (one of the direct products of L-Arg metabolism in human) serum levels were significantly lower in Becker muscular dystrophy patients [61]. This evidence, if confirmed in DMD patients, might give more support to the requirement of L-arginine and L-citrulline supplementation through diet.…”
Section: L-arginine and L-citrullinementioning
confidence: 99%
“…Utrophin has a similar function in the maintenance of the dystrophin-glycoprotein complex (DGC) integrity and myofibre structure. A widespread strategy to improve utrophin expression was to enhance the activity of the muscular isoform of nitric oxide synthase (NOS-μ) and NO synthesis by means of NO-donors administration, like L-arginine (or its precursor, L-citrulline [60,61]). NO is also critical to support mitochondrial function and biogenesis [62,63].…”
Section: L-arginine and L-citrullinementioning
confidence: 99%
“…In patients with Becker muscular dystrophy (BMD) the measured baseline creatinine-corrected urinary excretion rates were 48.8 (group I) and 53.0 (group II) µmol/mmol for DMA and 5.75 (group I) and 8.05 (group II) µmol/mmol for ADMA, and the corresponding DMA/ADMA molar ratios were 8.49 and 6.58 ( Table 1 ) [ 37 ]. Treatment of the BMD patients with metformin, L-citrulline and their combination did not result in appreciable changes in the urinary excretion rates of DMA and ADMA or their ratio [ 37 ].…”
Section: Urinary Dma and Adma In Children Adolescents And Adults mentioning
confidence: 99%
“…At physiological urinary concentrations, DMA (IC 50 , 590 µM), TMA (IC 50 , 53 µM) and creatinine (IC 50 , 6.8 mM) were found to inhibit the in vitro transport of metformin [ 60 ], suggesting a potential role of DMA in the renal reabsorption of organic cations. Yet, pharmacological metformin (3 × 500 mg/d) did not change the DMA excretion in patients with Becker muscular dystrophy (BMD), suggesting no mutual interaction of metformin and DMA on the renal OCT2 activity [ 37 ]. Pharmacological acetazolamide (5 mg/kg), which is a strong inhibitor of the activity of carbonic anhydrase (IC 50 , 12 nM for carbonic anhydrase II), seems to also not affect the excretion of DMA in the proximal tubule ( Figure 3 ).…”
Section: Statins Metformin L-arginine Catecholamines and The Prmentioning
confidence: 99%
“…[35][36][37][38][39][40] Alternatively, administration of L-citrulline, a dietary amino acid which is converted to L-arginine and has higher bioavailability than L-arginine alone, 41 improves clinical scores in patients with Becker muscular dystrophy. 42 Based on this evidence it is surprising that the effects of increasing NO production on GI function in vivo have not been examined. As compounds increasing NOS1 activity could improve GI function in muscular dystrophy and enhance quality of life for patients, we used video imaging and spatiotemporal (ST) mapping to interrogate GI dysfunction in mdx mice and determine the therapeutic potential of dietary L-arginine or L-citrulline supplementation.…”
Section: Introductionmentioning
confidence: 99%